Fc‐Gamma Receptor Polymorphisms Predispose Patients to Infectious Complications After Liver Transplantation. Issue 2 (30th October 2015) - Shimizu, S.; Tanaka, Y.; Tazawa, H.; Verma, S.; Onoe, T.; Ishiyama, K.; Ohira, M.; Ide, K.; Ohdan, H.
Abstract : We investigated the impact of polymorphisms in host innate immunoregulatory genes on the development of infectious complications after liver transplantation (LT). The single‐nucleotide polymorphisms (SNPs) of C1QA [276A/G], FCGR2A [131H/R], and FCGR3A [158F/V], genes encoding the Fc gamma receptor (FcγR), were analyzed in 89 living donor LT recipients in relation to the occurrences of postoperative infectious complications within 30 days after LT. Consistent with a lower affinity of the isoform encoded by FCGR3A [158F] to both IgG1 and IgG3, a significantly higher incidence of bloodstream infections (BSI) was observed in the FCGR3A [158F/V or F/F] than in the FCGR3A [158V/V] individuals. The combination of FCGR2A and FCGR3A SNPs further stratified the incidence of BSI, regardless of C1QA SNP. The predominant causative pathogen of BSI in the FCGR3A [158F/F or F/V] patients was gram‐positive cocci (73.3%), of which one third was methicillin‐resistant Staphylococcus aureus . No differences were observed in the incidence of fungal infections or in cytomegalovirus infections with respect to the three gene polymorphisms. Our findings indicate that FcγR SNPs are predisposing factors for BSI and can predict mortality after LT. This study provides a foundation for further prospective studies on a larger scale.